Purification of Drain Water and Distillation Residue from Organic Compounds, Transuranic Elements, and Uranium at the Chornobyl NPP - Rudenko, L.I.; Khan, V.E.; Kashkovskyi, V.I.; Dzhuzha, O.V. (Science and Innovation, 2024)
The research deals with the purification of drain water and distillation residue from organic (polymeric) compounds, transuranic elements, and uranium. The pretreatment method with the use of Sizol type coagulant-flocculant and catalytic oxidation with hydrogen peroxide and ultrafiltration has been proposed. This method prevents the evaporator coking by dust-suppressor and other organic substances vulcanized by heating. The removal of alpha-emitting radionuclides results in the increasing safety of the nuclear power plant operation.